دوافع وتحديات تطبيق اتفاقية بازل2 في المصارف التقليدية العاملة في سورية - إسماعيل ليندا; حاتم علي (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى إلقاء الضوء على دوافع وتحديات تطبيق اتفاقية بازل2 في المصارف التقليدية العاملة في سورية. لتحقيق هذا الهدف, قام الباحثان باستخدام منهجية المسح, حيث تم جمع البيانات باستخدام الاستبانة ثم تحليلها من خلال تطبيق مجموعة من الأساليب الإحصائية باستخدام برنامج SPSS. أظهرت النتائج أن المصارف العاملة في سورية تقوم بتطبيق اتفاقية بازل 2 استجابة لمتطلبات رقابية ودولية. فيما يتعلق بتحديات تطبيق الاتفاقية, تواجه هذه المصارف تحديات مرتبطة بتطبيق المحور الأول (المتطلبات الدنيا لرأس المال), حيث لا تملك بيانات تاريخية شاملة يمكن الاعتماد عليها لقياس المخاطر الائتمانية والتشغيلية والسوقية. يضاف إلى ذلك أنها غير حاصلة على تصنيف ائتماني دولي. كما توجد تحديات مرتبطة بتطبيق المحور الثاني (المراجعة الرقابية) تتعلق بشكل خاص بقلة عدد الكوادر العاملة في مجال الرقابة المصرفية, بالإضافة إلى التحديات المتعلقة بالظروف السياسية والأوضاع الاقتصادية السائدة. وأخيراً, أظهرت النتائج وجود علاقة عكسية بين واقع تطبيق بازل2 في المصارف التقليدية العاملة في سورية وبين كل من التحديات المرتبطة بتطبيق المحاور الثلاثة للاتفاقية وتلك المرتبطة بالظروف السياسية والاقتصادية. كما توجد علاقة عكسية بين واقع التطبيق والتحديات المرتبطة بالموارد المادية والبشرية في المصارف العامة فقط. This research aims to shed light on the motives and the challenges of the application of Basel II in banks operating in Syria. To achieve this goal, the researcher used the survey methodology, where the data was collected using a questionnaire and then analyzed by applying a set of statistical methods using the SPSS program. The results revealed that the banks operating in Syria are applying the Basel II Accord in response to regulatory and international requirement. With respect to the challenges of the application of the Accord, these banks face the challenges associated with the application of the first pillar (minimum capital requirements), as these banks do not have comprehensive historical data that can be relied on to measure credit, operational and market risks. In addition to the fact that they do not hold any international credit rating. There are also challenges associated with applying the second pillar (supervisory review), particularly related to the low number of working-staff in the field of banking supervision, in addition to the challenges of the political circumstances and the prevailing economic conditions. Finally, the results showed an inverse relationship between the reality of the Basel II application in conventional banks operating in Syria and between each of the challenges associated with implementing the three pillars of the Accord and those associated with political and economic conditions. There is also an inverse relationship between the reality of the implementation and the challenges associated with the material and human resources merely in public banks.